The Impact of Toxic Leadership and Job Insecurity in Predicting Turnover Intention Levels - Oktaviani Permatasari; Huda, Khasbulloh (PRAGMATIS, 2026)
Human resource stability is a key pillar in maintaining operational continuity in engineering companies that demand high precision. The purpose of this study is to disseminate and analyse the influence of job insecurity and toxic leadership on employee turnover intention at PT. Gajah Mada Teknik Mojokerto. The very high employee desire to move jobs challenges the stability of engineering company operations. This study was conducted quantitatively using an associative approach. This study involved all employees of PT Gajah Mada Teknik Mojokerto, yielding a saturated sample of 100 respondents. Data were collected through the distribution of questionnaires tested with a Likert scale. Data analysis was performed using multiple linear regression in SPSS. The results of the study indicate that, to some extent, Toxic Leadership has a positive and significant effect on Turnover Intention. Likewise, Job Insecurity has a positive and significant effect on Turnover Intention. Simultaneously, both variables have a significant effect on predicting employee turnover intention with a coefficient of determination of 36.1%. This finding implies that the management of PT. Gajah Mada Teknik needs to improve its managerial leadership style and ensure job security to reduce employee turnover. This study suggests that the management of PT. Gajah Mada Teknik Mojokerto must implement a holistic approach to reduce employee turnover. Improvements include reforming its management culture and ensuring job security through contract transparency. To create a healthy work environment and improve talent retention and long-term organisational productivity, the company must implement more humanistic and supportive leadership training.